Can Cotard Syndrome Be Induced?: Illustration With a Rare Case of Potential Organ Transplant. Issue 4 (April 2023) - Stip, Emmanuel; AlAhbabi, Mohammed; Arnone, Danilo; Abdel Aziz, Karim; Amiri, Leena; Javaid, Syed Fahad
Abstract: Cotard syndrome is a rare condition characterized by delusions ranging from a belief that one has lost organs to insisting that one has lost one's soul or is dead. This is the report a case of a 45-year-old man who was comatose after an attempted suicide. This was initially diagnosed as brain death and use of his organs for transplantation was actively considered. However, he awakened days later with new-onset Cotard syndrome. It remains difficult to know the link, unconscious or conscious, between this patient's delusions and the fleeting intention of doctors who intended to transplant his organs. This is the first description of a coincidence between delusional denial of an organ and the potential medico-surgical act of having an organ removed. This case is an opportunity to revisit the philosophical concepts of negation and nihilism. A multidisciplinary reflection is needed to give meaning to other clinical presentations.